Enhancing Autobiographical Memories through Mindfulness-Based Cognitive Training: An Intervention for Depression Adolescents during the COVID-19 Pandemic - bolook sahragard , Soolmaz; Shokouhi, Zeinab; Sheykhiani kha, Fateme; Naderi , Fatemeh; Shirzad Tularoudi , Mohammad Sadegh; Seyed Jafari , Javad (Shahroud Journal of Medical Sciences, 2022)
Background: The coronavirus [coronavirus disease 2019 (COVID-19)] pandemic has introduced extraordinary life changes and stress, particularly in adolescents and young adults. This study aimed to evaluate the effectiveness of mindfulness-based cognitive therapy group training on improving autobiographical memories in adolescents with depression during Covid-19.Methods: This research was a quasi-experimental study and a pre-test, post-test with a control group. The statistical population of this study consisted of all adolescent females with depression in the education of the 13th district of Tehran in 1400. The sampling process applied in this study was purposeful. Regular random sampling from among 240 female students in junior high school, 40 people (20 in the experimental group and 20 in the control group) were selected according to the depression score. The Autobiographical Memories test and Beck Depression Inventory were performed as a pre-test on the participants, then the experimental group received 8 sessions of mindfulness group training intervention and at the end of sessions, the research tool as a post-test was administered on both groups. Data were analyzed by SPSS-20 software using analysis of covariance. The significant level was set at 0.05.Results: Based on the results, the implementation of the independent variable on improving episodic memory dimension (Pvalue<0.001, F=12.430 (24 and 1) and semantic dimension (Pvalue<0.001, F=11.134 (24 and 1) in adolescents with depression was effective. Therefore, mindfulness-based cognitive therapy group training has been effective in strengthening episodic memory and semantic dimension in adolescents with depression.Conclusions: The result of the study showed that mindfulness-based cognitive therapy had a significant effect to improve episodic memory in adolescents with depression during the COVID-19. Therefore, this study suggests that therapists use this approach properly to reduce depression.Keywords: Mindfulness-based cognitive therapy group, Autobiographical memories, Adolescents, Depression.